Inferior pancreaticoduodenal artery false aneurysm: a rare cause of gastrointestinal bleeding diagnosed by three-dimensional computed tomography - Colak, M. C.; Kocaturk, H.; Bayram, E.; Karaca, L. (Singapore Medical Assoc, 2009)
We report a 57-year-old man who presented with a two-month history of persistent epigastric pain associated with indigestion, weight loss and jaundice. Contrast-enhanced computed tomography revealed a large pseudoaneurysm 87 mm x 68 mm in diameter, with its origin from the inferior pancreaticoduodenal artery of the superior mesenteric artery and in continuity with an ectatic gastroduodenal artery. The aneurysmal mass exerted direct pressure over the head of the pancreas, common bile duct and duodenum, causing obstruction. Non-selective abdominal angiography confirmed the aneurysm stemming from the inferior pancreaticoduodenal artery. Because of the obstructive symptoms and the size of the aneurysm, surgery was planned, but the patient refused and died from massive gastrointestinal bleeding one month later.
Keywords: computed tomography; gastrointestinal haemorrhage; inferior pancreaticoduodenal artery; pancreaticoduodenal artery rupture; pseudoaneurysm